Analýza vstupu ČR do EU z hlediska dopravy - Kampf, Rudolf (Univerzita Pardubice, 2001)
Republic by means of the matrix SWOT and sets strategic aims and principles for successful integration into the European Union. There are also emphasized priorities of the whole sector of transport. Mathematical methods were used for a sketch of the optimalization of the regional-transport service by public transport. There is also elucidated present-day transport politics of the Czech Republic. For this reason the contribution includes some tables and graphs which reflect well the development of the investments in transport. At the end of the article the author states, using the analytic method SWOT, that the advantages of the integration into the EU predominate over the disadvantages owing mainly to the increasing of the competition.
Keywords: dopravní politika; Česká Republika; Evropská Unie; vstup